2010
DOI: 10.1007/s12185-010-0600-2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy in a patient with multiple myeloma

Abstract: Progressive multifocal leukoencephalopathy (PML) is a neurological disease that affects immunodeficient patients. We describe here a case of 64-year-old man with IgD type multiple myeloma (MM) who developed progressive neurological symptoms. T(2)-weighted magnetic resonance imaging of the brain showed a hyperintense non-enhancing lesion in the left frontal lobe, and analysis of the cerebrospinal fluid by polymerase chain reaction revealed the presence of John Cunningham virus (JCV) DNA. Histopathological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Based on our literature review, nine autopsy cases have been reported from Japan in English in the past 30 years, [9][10][11][12][13][14][15][16][17] and the present paper is the second autopsy case report of rituximab-associated PML in Japan (Table 1). 17 The key diagnostic factors that can distinguish PML from the disorders previously mentioned, are predisposition to the disease and the histological findings.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Based on our literature review, nine autopsy cases have been reported from Japan in English in the past 30 years, [9][10][11][12][13][14][15][16][17] and the present paper is the second autopsy case report of rituximab-associated PML in Japan (Table 1). 17 The key diagnostic factors that can distinguish PML from the disorders previously mentioned, are predisposition to the disease and the histological findings.…”
Section: Discussionmentioning
confidence: 82%
“…Based on our literature review, nine autopsy cases have been reported from Japan in English in the past 30 years, and the present paper is the second autopsy case report of rituximab‐associated PML in Japan (Table ) …”
Section: Discussionmentioning
confidence: 90%
“…Akiyama et al describe the role of possible T cell dysfunction in the pathogenesis of PML, which is relevant in this particular case as multiple myeloma is known to induce severe immunosuppression and cause T cell dysfunction 7. Raisch et al also report that PML could be associated with the T cell and/or B cell dysfunction causing the failure to eliminate JCV, which is perhaps why drugs which cause such dysfunction (such as natalizumab, rituximab and mycophenolate) are implicated in the development of the disease 8 9…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, PML in patients with multiple myeloma (MM) is rare; only a few cases were reported in the 1970s, and none have been reported since. 10 Characteristic pathologic findings include lytic infection of the oligodendrocytes, which are swollen with enlarged densely basophilic nuclei filled with eosinophilic inclusion bodies. JCV also infects the astrocytes, which are also enlarged and contain numerous enlarged processes.…”
Section: Discussionmentioning
confidence: 99%